Scalp cooling for reducing alopecia in gynecology oncology patients treated with dose-dense chemotherapy: A pilot project - Cristina Mitric; Brian How; Emad Matanes; Zainab Amajoud; Hiba Zaaroura; Hai-Hac Nguyen; Angela Tatar; Shannon Salvador; Walter H. Gotlieb; Susie Lau (Elsevier, 2021)
Objective: Determine the efficacy of scalp cooling for the prevention of chemotherapy-induced alopecia in gynecology oncology patients. Methods: This prospective pilot study included patients diagnosed with a gynecological malignancy that received DigniCap™ scalp cooling. Patients were divided into two groups based on chemotherapy regimen: Carboplatin with area under the curve (AUC) 5-6 every three weeks and (1) conventional Paclitaxel 175 mg/m2 every three weeks or (2) Paclitaxel 80 mg/m2 weekly. A 1-10 visual analogue scale (1 no hair loss, 10 - complete hair loss) was used to assess degree of hair loss by patients themselves and by a certified dermatologist using photographs. Changes in quality of life and body image were measured using the European Organization for Research and Treatment of Cancer quality of life questionnaire version 3 (EORTC QLQ-C30) and the Body Image Scale (BIS) for cancer patients. Results: Hair preservation occurred with use of a scalp cooling device for patients receiving weekly Paclitaxel (n = 20), but not conventional every three weeks Paclitaxel (n = 8). Ten of 15 patients (66.7%) in the dose-dense group lost less than 50% of their hair based on self-assessment and 14 of 16 (87.5%) based on dermatologist assessment. No patient in this group acquired a cranial prosthesis (wig). There was no difference between groups in terms of quality of life (QoL) and BIS scores. Conclusion: Scalp cooling may allow for hair preservation in gynecology oncology patients receiving Carboplatin AUC 5-6 and weekly Paclitaxel 80 mg/m2 combination chemotherapy.